Distribution of aquatic mosses in the Soya Coast region, East Antarctica - Imura, Satoshi; Bando, Tadashi; Seto, Koji; Ohtani, Shuji; Kudoh, Sakae; Kanda, Hiroshi (National Institute of Polar Research, 2003)
P(論文) The distribution of aquatic mosses among 73 lakes in the Soya Coast region, East Antarctica, was surveyed. Two species of mosses, Bryum pseudotriquetrum and Leptobryum sp. were found at the bottom of lakes. B. pseudotriquetrum was found in 38 lakes (52.1%), mainly in freshwater lakes throughout the study area. Leptobryum sp. was found in 26 lakes (35.6%) in a rather restricted area, and mainly in relatively saline lakes. departmental bulletin paper